Prevalence of dental caries and associated risk factors among schoolchildren in an educational institution in Chiclayo, Perú - Córdova-Sotomayor, Daniel (2017)
Objective: To determine the prevalence of dental caries and its association with risk factors in schoolchildren aged 6 to 11 years. Materials and Methods: This study design was not experimental, prospective and cross conducted during the months of April and May 2016 in a population of 109 students. The sample consisted of the students who attended regularly, accepted the oral examination and had the informed consent signed by their parents. The criteria for dental caries rates according to WHO recommended was used. To identify risk factors questionnaire caries risk assessment proposed by the American Society of Pediatric Dentistry was used. Chi-square test and Fisher exact test was used, a multivariate logistic regression model was formed, the odds ratio (OR). Results: This research showed that the only factors significantly associated with dental caries were the loss of teeth in parents and siblings (p = 0.0354), (OR = 4.72 (95% CI: 1, 11- 20, 03)) and consumption of sugary liquids or